Solubility of amino acids in mixed solvent systems - Ferreira, Luísa (2010)
The solubilities of L-serine, L-threonine and L-isoleucine in the aqueous systems of ethanol, 1-propanol and 2-propanol were measured in the temperature range between 298.15 K and 333.15 K by means of a gravimetric method and a spectrophotometric technique based on a ninhydrin reaction. The solubility data from this work and from literature were used to explore the potentialities of the application of the excess solubility approach with the NRTL [1], modified NRTL [2], modified UNIQUAC [3, 4] equations and the model presented by Gude et al. (1996) [5, 6]. These four models give a global average relative deviation of 12.2 %, 12.0 %, 15.1 %, and 16.2 % for correlation and 16.3 %, 14.6 %, 27.3 %, and 22.0 % for prediction, respectively.